A Life‐Course Model of Trauma Exposure and Mental Health Among Low‐Income Survivors of Hurricane Katrina. Issue 6 (20th August 2020) - Lowe, Sarah R.; Raker, Ethan J.; Arcaya, Mariana C.; Zacher, Meghan L.; Waters, Mary C.; Rhodes, Jean E.
Abstract: Prior research has provided robust evidence that exposure to potentially traumatic events (PTEs) during a disaster is predictive of adverse postdisaster mental health outcomes, including posttraumatic stress symptoms (PTSS) and nonspecific psychological distress (PD). However, few studies have explored the role of exposure to other PTEs over the life‐course in shaping postdisaster mental health. Based on the broader literature on trauma exposure and mental health, we hypothesized a path analytic model linking predisaster PTEs to long‐term postdisaster PTSS and PD via predisaster PD, short‐term postdisaster symptoms, and disaster‐related and postdisaster PTEs. We tested this model using data from the Resilience in Survivors of Katrina study, a longitudinal study of low‐income, primarily non‐Hispanic Black mothers exposed to Hurricane Katrina and assessed before the disaster and at time points 1, 4, and 12 years thereafter. The models evidenced a good fit with the data, RMSEA < .01–.04, CFIs > .99. In addition, 44.1%–67.4% of the effect of predisaster PTEs on long‐term postdisaster symptoms was indirect. Descriptive differences were observed across models that included PTSS versus PD, as well as models that included all pre‐ and postdisaster PTEs versus only those that involved assaultive violence. The results suggest the importance of incorporating disaster preparedness in clinical work with trauma survivors and the value in attending to other lifetime PTEs when working in postdisaster contexts. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Un modelo de ciclo de vida de trauma y salud mental entre sobrevivientes de bajos ingresos del huracán MODELO DEL CICLO DE VIDA DE SALUD MENTAL POSTERIOR A DESASTRES Investigaciones anteriores han proporcionado pruebas sólidas de que la exposición a eventos potencialmente traumáticos (EPT) durante un desastre predice los resultados adversos de salud mental posteriores al desastre, incluidos los síntomas de estrés postraumático (SEPT) y el estrés psicológico inespecífico (EP). Sin embargo, pocos estudios han explorado el papel que tiene la exposición a otras EPT durante el curso de la vida en la configuración de la salud mental posterior al desastre. Basándonos en la literatura más amplia sobre la exposición al trauma y la salud mental, planteamos la hipótesis de un modelo analítico de trayectoria que vincula los EPT previos al desastre con los SEPT y el EP a largo plazo después del desastre a través del EP previo al desastre, los síntomas posteriores al desastre a corto plazo y los EPT relacionados con el desastre y después del desastre. Probamos este modelo utilizando datos del estudio de Resiliencia en sobrevivientes del Katrina, un estudio longitudinal de madres afroamericanas de bajos ingresos, principalmente no hispanas, expuestas al huracán Katrina y evaluadas antes del desastre y a los 1, 4 y 12 años después. Los modelos evidenciaron un buen ajuste con los datos, RMSEA <.01 – .04, CFIs > .99. Además, entre el 44.1% y el 67.4% del efecto de los EPT previos al desastre sobre los síntomas posteriores al desastre a largo plazo fue indirecto. Se observaron diferencias descriptivas entre los modelos que incluían Los SEPT versus EP, así como modelos que incluían todas los EPT antes y después del desastre versus solo aquellos que involucraban violencia agresiva. Los resultados sugieren la importancia de incorporar la preparación para desastres en el trabajo clínico con sobrevivientes de trauma y el valor de atender a otros EPT a lo largo de la vida cuando se trabaja en contextos posteriores a desastres. 抽象: 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 JOTS‐20‐0032.R1 Lowe A Life‐Course Model of Trauma Exposure and Mental Health Among Low‐Income Survivors of Hurricane Katrina Traditional Chinese 標題: 低收入的颶風卡特里娜生還者當中, 創傷經歷和心理健康的生命歷程模型 撮要: 過往研究已提供可靠證據, 證明在災難中經歷潛在創傷事件(PTE), 能預測災後心理健康, 包括創傷後壓力症狀(PTSS)和非特殊的心理悲痛(PD)。可是, 目前少有研究探討在生命中經歷其他PTEs, 對災後心理健康構成的影響。我們以較廣泛的創傷經歷及心理健康文獻為基礎, 我們假設了一個路徑分析模型, 經由災前PD、短期災後症狀、災難相關及災後PTE, 把災前PTE跟長期的災後PTSS及PD連繫起來。我們利用了《卡特里娜生還者的恢復力》(Resilience in Survivors of Katrina) 研究中的數據, 來測試這個模型。這個縱貫研究主要對象為經歷過颶風卡特里娜的低收入、非西班牙裔黑人母親。樣本在災前, 以及災後1、4及12年接受評估。結果, 模型與這些數據吻合程度良好, RMSEA < .01–.04, CFIs > .99。此外, 災前PTEs對災後長期症狀的影響中, 44.1%至67.4%為間接效應。所有包含PTSS比對PD的模型, 以及包括了所有災前及災後PTE比對只含暴力襲擊的模型, 都出現描述上的差異。這些結果反映, 為創傷生還者提供的臨床服務中包含災難應變的重要性, 以及在生還者災後處理其其他終身PTEs的意義。 Simplified Chinese 標题: 低收入的飓风卡特里娜生还者当中, 创伤经历和心理健康的生命历程模型 撮要: 过往研究已提供可靠证据, 证明在灾难中经历潜在创伤事件(PTE), 能预测灾后心理健康, 包括创伤后压力症状(PTSS)和非特殊的心理悲痛(PD)。可是, 目前少有研究探讨在生命中经历其他PTEs, 对灾后心理健康构成的影响。我们以较广泛的创伤经历及心理健康文献为基础, 我们假设了一个路径分析模型, 经由灾前PD、短期灾后症状、灾难相关及灾后PTE, 把灾前PTE跟长期的灾后PTSS及PD连系起来。我们利用了《卡特里娜生还者的恢复力》(Resilience in Survivors of Katrina) 研究中的数据, 来测试这个模型。这个纵贯研究主要对象为经历过飓风卡特里娜的低收入、非西班牙裔黑人母亲。样本在灾前, 以及灾后1、4及12年接受评估。结果, 模型与这些数据吻合程度良好, RMSEA < .01–.04, CFIs > .99。此外, 灾前PTEs对灾后长期症状的影响中, 44.1%至67.4%为间接效应。所有包含PTSS比对PD的模型, 以及包括了所有灾前及灾后PTE比对只含暴力袭击的模型, 都出现描述上的差异。这些结果反映, 为创伤生还者提供的临床服务中包含灾难应变的重要性, 以及在生还者灾后处理其其他终身PTEs的意义。